Pemanfaatan Air Jeruk Nipis (Citrus aurantifolia) Dalam Peningkatan Kualitas Nata De Cane - Dinda Marthalia; Nurhaida Widiani; Ika Listiana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to analyze the effect of adding lime juice (Citrus aurantifolia) on the quality of Nata de Cane. The research was conducted using a completely randomized design with five lime juice concentrations (0%, 1%, 2%, 3%, and 4%) and a constant Acetobacter xylinum starter concentration of 30%. The observed parameters included fiber content, moisture content, sugar content, vitamin C, yeast and mold counts, and organoleptic properties. The results showed that the addition of lime juice had no significant effect on fiber, moisture, and sugar content. However, there was a significant increase in vitamin C levels, from 0.45 mg/100 g in the control to 4.80 mg/100 g in the 4% treatment. The organoleptic test indicated that the 4% lime juice treatment achieved the highest scores for color, aroma, taste, and texture. These findings demonstrate that the addition of lime juice can increase vitamin C content and improve the sensory quality of Nata de Cane. Therefore, lime juice addition is effective as a natural pH regulator and nutritional enhancer in fermented food production.